Analisis Pengaruh Kebijakan Utang, Kepemilikan Saham Publik, Risiko Kebangkrutan Terhadap Biaya Agency - Diah Anugrah Sharasanti (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2016)
Financial management strategic decision that can not be ignored is the decision regarding the dividend policy, investment, and financing, are closely associated with the company's goal is to optimize the value of the company. However, the goals are often not carried out in connection with the separation of the functions of ownership and management functions of the company, which makes the manager to act independently and not in line with company objectives. Conflicts over the source of the problem that causes the cost of the agency (agency cost), ie all costs incurred to carry out surveillance (monitoring) on the performance of managers. The research objective was to determine whether the debt ratio, managerial ownership, and earnings volatility significantly affect the cost of agency. Results showed that the ratio of debt, stock ownership by top managers, and earnings volatility significantly not affect the cost of agency.